The ideal carer role: gendered expectations in childhood ethnography. Issue 1 (2nd January 2020) - Bailey, Denise E.
ABSTRACT: Drawing on data from a preschool-based ethnography that examined both teachers and children, this paper explores gendered elements of adult–child interactions in the preschool classroom. The author describes a methodological approach that acknowledges the provision of helpfulness as a common, everyday expectation that the children had of their teachers, enacted through what she calls the 'ideal carer role'. Adopting the role allowed her to gain insight into the everyday expectations of children and adults within the shared classroom culture, as well as some contexts in which children utilised adult power. Reflecting on the adoption of the role, the author also explores the ethics of enacting care, helpfulness, discipline and pedagogy as part of an ethnography of adult–child relations.